High on arrival : a memoir - Phillips, Mackenzie; Liftin, Hilary (New York : Simon Spotlight Entertainment, 2009)
The actor-musician-mother shares her lifelong battle with personal demons, incest, and near-fatal addictions in this astounding, outrageous, and often tender life story.
Keywords: Phillips, Mackenzie; Actors -- United States -- Biography; Singers -- United States -- Biography